Forty conferences - Kubilius, Jonas (Lietuvos matematikos rinkinys, 1999)
The situation of mathematical life in Lithuania before the rise of the Lithuanian Mathematical Society and the circumstances of the founding of the Society are described. The article gives a survey of activities of the Society until last time.